LOFAR-style reconstruction of cosmic-ray air showers with SKA-Low - Corstanje, A.; Bouma, Sjoerd; Buitink, S.; Desmet, M.; Hörandel, J. R.; Huege, T.; Laub, Philipp; Mulrey, K.; Nelles, Anna; Scholten, O.; Terveer, Karen; Thoudam, S.; et al. (Physical Review D, 2025)
Cosmic-ray air shower detection with the low-frequency part of the Square Kilometre Array (SKA) radio telescope is envisioned to yield very high precision measurements of the particle composition of cosmic rays between 1016 and 1018 eV. This is made possible by the extreme antenna density of the core of SKA-Low, surpassing the current most dense radio air shower observatory LOFAR by over an order of magnitude. In order to make these measurements, the technical implementation of this observation mode and the development of reconstruction methods have to happen hand in hand. As a first lower limit of what is obtainable, we apply the current most precise reconstruction methods as used at LOFAR to a first complete simulation of air shower signals for the SKA-Low array. We describe this simulation setup and discuss the obtainable accuracy and resolution. A special focus is put on effects of the dynamic range of the system, beam-forming methods to lower the energy threshold, as well as the limits to the mass composition accuracy given by statistical and systematic uncertainties.
CRIS-Team Scopus Importer:2025-12-12